Microbiome, innate Immunity, and esophageal adenocarcinoma - Baghdadi, Jonathan (Clin Lab Med, 2014)
With the development of culture-independent technique, a complex microbiome has been established and described in the distal esophagus. Over recent decades, the incidence of esophageal adenocarcinoma (EAC)—a relatively rare cancer with high mortality—has increased dramatically in the United States. Several studies documenting an altered microbiome associated with EAC and its precedents (i.e., Barrett’s esophagus and reflux esophagitis) suggest that dysbiosis may be contributing to carcinogenesis, potentially mediated by interactions with toll-like receptors. Investigations attempting to associate viruses, in particular human papilloma virus, with EAC have not been as consistent. Regardless, currently available data is cross-sectional and therefore cannot prove causal relationships. Prospectively, microbiome studies open a new avenue to the understanding of the etiology and pathogenesis of reflux disorders and EAC.